Impact of donor lung bacteria detected by rapid on-site evaluation on early post-transplant outcomes in lung transplant recipients - Tianyang Liu; Yunxiang Zhang; Hang Yang; Xiaoshan Li; Hongmei Wang; Li Fan; Dong Wei; Bo Wu (Asian Journal of Surgery)
Background: Rapid On-Site Evaluation (ROSE) has been widely used in clinical applications. However, in the field of lung transplantation, there have been no comparative experiments to confirm and quantify its effectiveness. To this end, ROSE was used to detect donor lung infection or colonization and analyze its influence on the prognosis of lung transplantation. Methods: This study retrospectively analyzed 15 patients who received our center from March 2023 to May 2023. Fibrobronchoscopy and ROSE of bronchoalveolar lavage fluid(BALF) were performed. Postoperative survival rate index was collected for prognostic analysis. The coincidence rate of ROSE and traditional test culture was compared. Results: ① The 15 BALF samples were divided into infection group and colonization group according to the presence of infection and phagocytosis.② The average time of ROSE report was 10.40 min, and the average time of Sputum culture test report was 4663 min, and the difference between the two groups was statistically significant (p < 0.01). ③ The results of ROSE's evaluation of donor lung infection were in good agreement with those of traditional Sputum culture, and the difference was statistically significant (p < 0.01). (4) There were no significant differences in postoperative survival rate index between the infection group and the colonization group after targeted antibiotics were applied in advance. Conclusion: ROSE has a high heterogeneity in the evaluation of donor lung transplantation infection. It can be used as one of the important auxiliary examination techniques before and after lung transplantation.